2018
DOI: 10.3390/medicina54060104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Body Composition of Caucasian Young Normal Body Mass Women, Measured in the Follicular Phase, Depending on the Carbohydrate Diet Level

Abstract: Background and objectives: Some publications indicate the possibility of the influence of meal nutritional value on results of bioelectrical impedance, and of the relation between the long-term carbohydrate intake and body composition. The aim of the presented study was to evaluate the influence of long-term intake of carbohydrates on body composition results assessed using the bioelectrical impedance of Caucasian young women with normal body mass, who were in the follicular phase of their menstrual cycle. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
6
1
Order By: Relevance
“…In contrast, in the present study, there were no differences in ICF (MD ± SD, 0.06 ± 0.51 L), whereas another study demonstrated a significantly higher ICF during the follicular phase compared with the menstrual phase (MD, ~0.93 L) (16); this disparity may have been influenced by underlying technological differences in that multifrequency BIA devices are often limited to measuring impedance at 2–6 frequencies and using equations, while BIS more accurately measures impedance at infinite frequencies and uses a Cole Model to determine total and compartmental fluid content. In addition, a recent investigation observed that high carbohydrate intake is associated with higher intracellular water, which was not assessed in either the present study or the investigation by Mitchel and colleagues (16,18).…”
Section: Resultscontrasting
confidence: 78%
“…In contrast, in the present study, there were no differences in ICF (MD ± SD, 0.06 ± 0.51 L), whereas another study demonstrated a significantly higher ICF during the follicular phase compared with the menstrual phase (MD, ~0.93 L) (16); this disparity may have been influenced by underlying technological differences in that multifrequency BIA devices are often limited to measuring impedance at 2–6 frequencies and using equations, while BIS more accurately measures impedance at infinite frequencies and uses a Cole Model to determine total and compartmental fluid content. In addition, a recent investigation observed that high carbohydrate intake is associated with higher intracellular water, which was not assessed in either the present study or the investigation by Mitchel and colleagues (16,18).…”
Section: Resultscontrasting
confidence: 78%
“…Combined with the previous results, it could give support for the mediating role of BMR between carbohydrates and SMI. A long-term reduction in carbohydrate intake may cause the transfer of ICW to the extracellular space, resulting in high ECW/ICW and ECW/TBW [ 42 ]. This could support the moderating effects of body water distribution on the indirect relationship between carbohydrates and SMI through BMR.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements were taken by a professional dietitian using BIA 101/ASE (Akern Srl, Firenze, Italy). According to the commonly-applied rules, the measurements were obtained in the morning, in the fasting state (the last meal was to be consumed and the last beverage was to be drunk at least 8 h before the measurement), after a day when no excessive physical activity was performed; that is, no training was conducted on the previous day [45]. The measurements were taken after removing shoes and jewelry, and when the participants were in light underwear or sportswear with no metal elements.…”
Section: Methodsmentioning
confidence: 99%